Efficacy of an internet-based program (MS Intakt) to promote physical activity after inpatient rehabilitation in persons with multiple sclerosis – a randomized controlled study - Bures, Anna-Karolina; Kuld, Sarah; Weiland, Ann-Christin; Tallner, Alexander; Gusowski, Klaus; Pfeifer, Klaus; Flachenecker, Peter (European Comittee for treatment and research in multiple sclerosis (ECTRIMS), 2017)
Background. Multimodal rehabilitation improves symptoms in persons with multiple sclerosis (PwMS), but these effects diminish with time, despite the well-known positive impact of exercise on fatigue and mobility. We evaluated the efficacy of a 3-month, internet-based e-training program (“MS Intakt”)1 on fatigue, quality of life and mobility in PwMS after inpatient rehabilitation. Methods. Inclusion criteria:  PwMS admitted to inpatient rehabilitation, no relapse / steroid therapy within the last 30 days,  Fatigue (WEIMuS score ≥ 32), age ≥ 18 years, EDSS ≤ 6.0 E-Training group (EG): 3-month home training program,supervised via internet by sport therapists directly after rehabilitation Control group (CG): usual care alone Primary outcome: Fatigue after 3 months (WEIMuS questionnaire2) Secondary outcomes: Quality of life (MSIS-29, EQ-5d), Mobility (2min walking test, 10m WT, Tinetti score), Neuropsychological parameters (alertness) Physical activity (standardized questionnaires), willingness to pay Measurements: T0:within the first week after admission (Baseline), T1: end of rehabilitation (Discharge), T2: follow-up after 3 months (Month 3), T3: follow-up after 6 months (Month 6, via mail) Results: 84 PwMS were included, of whom 64 completed the study At baseline, median WEIMuS scores were higher (indicating a higher degree of fatigue) in EG than in CG, but decreased similarly at discharge in both groups. However, WEIMuS scores increased again in CG at both follow-up measurements, whereas in the etraining group, fatigue further improved at 3 and 6 months. Similarly, MSIS-29 scores were improved in both groups at discharge, but remained stable at month 3 only in the e-training group. The improvements in gait parameters were also more pronounced in EG, particularly for the 2-minute walking test Conclusion: The results of our study demonstrate that the effects of rehabilitation on fatigue, quality of life and mobility can be maintained with an internet-based home training program for up to 3 – 6 months. Further studies are needed to investigate whether longer-lasting programs may have more sustained effects on these disabling symptoms in PwMS.
Keywords: exercise training; multiple sclerosis; inpatient rehabilitation; internet-based